Protocol Modeling with Model Program Composition - Veanes, Margus; Schulte, Wolfram (FORTE'08, 2008)
Designing and interoperability testing of distributed, application-level network protocols is complex. Windows, for example, supports currently more than 200 protocols, ranging from simple protocols for email exchange to complex ones for distributed file replication or real time communication. To fight this increasing complexity problem, we introduce a methodology and formal framework that uses model program composition to specify behavior of such protocols. A model program can be used to specify an increment of protocol functionality with a coherent purpose, which can be understood and analyzed separately. The overall behavior of a protocol can be defined by a composite model program, which defines how the individual parts interoperate.